A Critical Analysis of the Fulfillment of the Intent Element in the Dissemination of Private Content under the Electronic Information and Transactions Crime, Based on Decision No. 805/Pid.Sus.2024/PN.Jkt.Sel.: Analisis Kritis Pemenuhan Unsur Kesengajaan Penyebarluasaan Konten Pribadi Dalam Tindak Pidana ITE Studi Putusan Nomor 805/Pid.Sus.2024/PN.Jkt.Sel - Rambe, Halgi Sujuangon Jhansen; Adhari, Ade (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid advancement of digital technology has increased legal challenges related to electronic information misuse, particularly within Indonesia’s Special Criminal Law governing Electronic Information and Transactions (EIT). Specific Background: Cases involving the dissemination of private content frequently raise questions regarding the fulfillment of intent or dolus as a requirement for criminal liability. Knowledge Gap: Judicial inconsistencies in assessing intent—especially in distinguishing intentional acts from negligence—indicate the need for deeper doctrinal analysis. Aims: This study critically examines the fulfillment of intent in the dissemination of private content under Article 27 ayat 1 jo. Article 45 ayat 1 of the EIT Law, based on Decision No. 805/Pid.Sus.2024/PN.Jkt.Sel. Results: The findings show that the court’s analysis relied on three key elements: actus reus, the absence of rights or consent, and mens rea reflected in the perpetrator’s awareness of wrongdoing, while also considering the defendant’s negligence or culpa. Novelty: This study exposes discrepancies between courtroom facts and judicial reasoning, revealing conceptual misalignment in applying intent within EIT cases. Implications: The research provides a clearer analytical framework for judges and legal practitioners to differentiate intentional wrongdoing from negligence in future EIT adjudications. Highlights: The study clarifies how intent is assessed in private-content dissemination cases under the EIT Law. Findings show discrepancies between courtroom facts and the court’s interpretation of intent. The research offers a clearer framework for distinguishing intent from negligence in future cases. Keywords: Intent, Negligence, EIT Law, Private Content, Criminal Liability